-4=s-4

Simple and best practice solution for -4=s-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=s-4 equation:



-4=s-4
We move all terms to the left:
-4-(s-4)=0
We get rid of parentheses
-s+4-4=0
We add all the numbers together, and all the variables
-s=0
s=0/-1
s=0

See similar equations:

| -4a+3+5a=11-25 | | m=234 | | −2=−4+t | | 11x+5=7x+41 | | 5+8=-13-2x | | 2x+6+135+25=180 | | 5/2k+8-11/2k=5k-4 | | 5=4-b | | 2m+2m=12 | | -21=-18x+33 | | 4x-8=5x+30 | | 38=3p+5 | | 5w=10=100 | | 16=2x+1-7 | | X^+2-3x+8=0 | | 28t^2-17t=0 | | 5=x+5,x=10 | | 2(v+16)=40 | | 9-2x-6x=62 | | 11x-17=65=180 | | 32x+5=44x-9 | | 8w−8=80 | | f/4-5=-5 | | 3.2x+11=1.2x-1 | | -14=23r−14=23 | | 6÷y=2 | | 2(8-y)+3=17 | | (6x+4)+(3x+1)=5x | | r-14=23r−14=23 | | 6=7z−22 | | -2(z+5)=-14 | | -17+b=-21 |

Equations solver categories